Not Like 1916, 25-29. 08. 2000. ESSE, Helsinki, Finland - Gjurgjan, Ljiljana Ina (2000)
The paper relies on R, Barthes’s definition of mythology as de policized speech in order to investigate two meaning given to Easter 1916. Yeats’s poem has attributed to the aesthetization of this tragic event, proclaiming that the terrible beauty was born. However, this hot rhetoric (S. Deane) has blocked the understanding of the later events in Northern Ireland. Therefore, in his novel Cal, M. Leverty has one of the characters claim “This is not like 1916” .Yet, the other person replies “But it was not like 1916 in 1916” pointing thus to the difference between the reality of the actual event and its later aesthetization.